POLITENESS PRINCIPLE OF ASSERTIVE ACT IN DEBATE BETWEEN DONALD TRUMP AND JOE BIDEN - Denisa Rizkia Haniva; Irman Nurhapitudin; Erfan Muhamad Fauzi (STKIP Siliwangi, 2021)
In presidential elections, debates are often held between presidential candidates to find out the arguments, vision and mission, as well as policies that will be carried out by presidential candidates in their country. In expressing statements in their debates, speakers often do not realize the important aspects of language that affect the image of presidential candidates in public, namely the aspect of politeness. In language, the politeness aspect is studied in pragmatic studies which study the speaker's speech intention which depends on the context. This research used descriptive qualitative method which emphasizes the description of the data. In this study, each data was analyzed by the politeness maxims contained in the speech, as well as the assertive function contained in the politeness speech. There are five politeness maxims and there are speeches that violate the politeness maxims contained in the speeches of presidential candidate debates, and there are five speech functions of speeches that contain politeness and violate politeness maxims. Each politeness utterances and violates politeness has a different assertive function.Keywords: Politeness Principle, Assertive Act, Politeness Maxim, Presidential Debate